E-Voting Meets Blockchain: A Survey - Maria-Victoria Vladucu; Ziqian Dong; Jorge Medina; Roberto Rojas-Cessa (IEEE Access, 2023)
The utilization of electronic voting systems for the election of public offices is becoming widespread globally. This trend can be attributed to the benefits provided by these systems, including remote voting capabilities and accelerated vote counting. Furthermore, electronic voting systems offer improved privacy and enhanced protection against voting bias. Blockchain technology enhances the robustness of the voting process through its immutable vote storage mechanism, thereby reducing the threat of vote tampering and safeguarding the legitimacy of elections. This technology has been adopted by countries such as Germany, Russia, Estonia, and Switzerland for use in their e-voting systems. This study provides a comprehensive overview of the blockchain-based e-voting systems currently being implemented by various countries and companies and proposed for academic research. Additionally, this study analyzes the challenges faced by blockchain e-voting systems and identifies areas for future research to enhance the trustworthiness of such systems.